Improving the Beginning Reading Skills of Slow Learner Students Through the Use of Animated Audio-Visual Media Powtoon in Indonesian Language Learning at Advent Elementary School (SD) - Purba, Epta; Pamungkas, Bayu (Perspektif Ilmu Pendidikan, 2025)
This study aims to improve the early reading skills of slow learner students through the utilization of Powtoon animated audio-visual media in Indonesian language instruction at SD Advent Sangatta. The specific objective of the research is to evaluate the effectiveness of animation media in capturing attention, enhancing comprehension, and stimulating learning motivation among students with special needs, particularly those who face difficulties in early reading. The method used is Classroom Action Research (CAR), conducted in two cycles. Each cycle consisted of planning, action implementation, observation, and reflection. The research subjects were four slow learner students in the first grade of SD Advent Sangatta. Data were collected through pretests, posttests, observations, interviews, and documentation, and were analyzed quantitatively using descriptive statistics and paired sample t-tests, as well as qualitatively through thematic analysis. The results show that the use of Powtoon media had a significant impact on improving the early reading abilities of slow learner students. The average pretest score of 35 increased to 65 in the posttest, showing an 85.71% improvement. Additionally, students demonstrated greater focus, motivation, and engagement during the learning process. Interviews and observations confirmed that the media made learning more enjoyable, easier to understand, and aligned with the learning characteristics of slow learners. Therefore, the use of animated media like Powtoon is recommended as an effective and inclusive instructional strategy for students with special educational needs. Keywords: slow learner, early reading, Powtoon media, audio-visual, Indonesian language learning.